The Role and Extend of Artificial Intelligence in Enhancing Volleyball Learning - Naji, Saif Alaa; Abdulqader, Neran Khaleel (Yayasan Insan Mulia Bima, 2025)
This study aims to explore the role and degree of artificial intelligence (AI) usage in enhancing the learning of volleyball among students in colleges of physical education. Specifically, it investigates students’ perceptions of AI's importance and the differences between undergraduate and postgraduate students in terms of their understanding and application of AI technologies. The descriptive method was employed, and the sample consisted of 200 undergraduate and 50 postgraduate students from various Iraqi universities. A 31-item questionnaire, divided into two axes. (1) the importance of AI in education and (2) the challenges of its implementation-was distributed during volleyball classes. The results showed that postgraduate students demonstrated a more consistent and logical understanding of AI's educational functions, particularly its flexibility, adaptability, and role in self-directed learning. In contrast, undergraduate students exhibited varied responses, indicating a lack of familiarity with some aspects of AI. Although the postgraduate group had higher mean scores, T-test results showed no statistically significant mean difference (p > 0.05) between the two groups.